Leigh Goodmark, Decriminalizing Domestic Violence: A Balanced Policy Approach to Intimate Partner Violence, University of California Press, 2018 - Porter, Antonia (feminists@law, 2019)
Review of Leigh Goodmark's Decriminalizing Domestic Violence: A Balanced Policy Approach to Intimate Partner Violence (University of California Press, 2018).